Voltammetric detection of trifluralin in tap water, fruit juice, and vegetable extracts in the presence of surfactants. Issue 10 (3rd October 2017) - Ferro, Érica Castro; Cardoso, Claudia A. L.; Arruda, Gilberto J.
ABSTRACT: This study describes a novel electrochemical method to determine the herbicide trifluralin in samples of water, fruit juice, and vegetable extracts in the presence of surfactants, using a glassy carbon electrode (GCE). In acidic media, trifluralin was irreversible on the glassy carbon electrode surface at −0.5 V vs. Ag/AgCl. Surfactant presence on the electrode–solution interface modified current intensities and shifted the reduction peak potential of trifluralin. Different types of surfactant and their concentrations were investigated. The anionic surfactant significantly enhanced the peak current intensity of trifluralin. Under optimal analytical conditions, an analytical curve was obtained in the concentration range of 0.48–32.20 µM. The limits of detection and quantification were estimated at 0.031 and 0.104 µM, respectively. The method was successfully applied to quantify trifluralin in samples of water, orange and tomato juice, and green pepper, carrot, and onion extracts, with recovery rates of 97.9–102.1%. The results were in good agreement with those obtained using high-performance liquid chromatography, indicating that the proposed electrochemical method can be employed to quantify trifluralin in various types foods, with sensitivity, specificity, selectivity and reproducibility.